Case Report: Treatment of facial pyoderma gangrenosum with Upadacitinib - Ge, Gai; Zhan, Lirui; Huang, Meng; Su, Fei; Chen, Jinbo; Dong, Jing (Frontiers in Medicine, 2025)
Pyoderma gangrenosum (PG) is a recurrent, painful, necrotizing ulcerative neutrophilic dermatosis. Facial PG (FPG) is a rare subtype of PG that is often misdiagnosed. A 20-year-old male with FPG showed improvement after treatment with a combination of prednisone and upadacitinib. Early diagnosis is crucial to avoid misdiagnosis.